ANALISIS KOMPETENSI GURU DALAM PENERAPAN KURIKULUM MERDEKA DI SDN 47 CAKRANEGARA - SAFITRI, SULISTIANA; Nurhasanah; Rahmatih, Aisa Nikmah; Makki, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze how the teacher's competence in implementing the Merdeka curriculum and what are the difficulties experienced by teachers in implementing the Merdeka curriculum at SD Negeri 47 Cakranegara in the 2024-2025 academic year. This research uses a qualitative approach with descriptive methods. The subjects of this research are grade I teachers and grade IV teachers. This research was conducted using observation, documentation, and interview methods in obtaining research data related to teacher competence in implementing the Merdeka curriculum. The results showed that the grade 1 teacher has quite good pedagogical competence while the pedagogical competence of the grade 4 teacher shows that it is still not good, this can be seen from the many indicators that have not been implemented. In personal and social competencies, it shows that grade I and IV teachers have personal and social competencies that are well implemented. While professional competence shows that grade I and IV teachers have good professional competence, but grade IV teachers are less able to develop learning materials in the classroom. The difficulties experienced by SD Negeri 47 Cakranegara teachers in implementing the Merdeka curriculum include; difficulties in analyzing modules, utilizing technology, difficulties in conducting differentiated learning, difficulties in the latest and problem-based methods, and difficulties in implementing P5 implementation.